Benchmarking and Performance Analysis of Software Defined Networking Controllers in Normal and Failsafe Operations using Multiple Redundant Controllers - Ayman Haggag , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software Defined Networking (SDN) has a great impact on networks and data communication. The future of the infrastructure for networks will be different. Network administrators will no longer need to configure every router or switch, and it will be unnecessary to program or write their configurations individually. A central control device is used to control the entire network. In this research, we will build network topologies using open flow switches connected to open flow controllers that will provide flow tables for switches. We will use Benchmarking and compare the performance of different popular open flow controllers, OpenDaylight (ODL), Open Network Operating System (ONOS), RYU, Floodlight, POX, and Trema. We will show how this new infrastructure drastically improves network performance and several legacy protocols, like Spanning Tree Protocol, are rendered obsolete. In larger multiple controller networks, the network resilience against controller failure with the utilization of multiple redundant controller connections is demonstrated.